PREDIKSI KELULUSAN MAHASISWA DENGAN METODE ALGORITMA C4.5 - Jajam Haerul Jaman (SYNTAX Jurnal Informatika)
The world of education is a valuable asset for the development of science that continues to grow and constantly require appropriate analyzes as a current evaluation of materials for the development of education itself, in this case I tried to do research in predicting graduation with C45 algorithm method, while the research object is a student, the results obtained turned out its outline is the effect of gender on very high graduation, in this case the female gender who received a high percentage compared to male gender.Â Keywords: Algoritma C45, Data Mining, Decision Tree